Lyric weathering: reading poetry in the age of bewilderment. Issue 12 (2nd December 2021) - Cotton, Jess
ABSTRACT: The language of ecocriticism is often one of mourning and melancholia: a mourning for the end of nature that has already come to pass. The emergent field of ecopoetics is driven, similarly, by a language of grief and its most emblematic forms are, accordingly, elegies. In this article, I make a case for reorienting the language of ecocriticism to make it more hospitable to the affects – bewilderment and anxiety: negative affects that are characterised by confusion and by an inability to act – which, I contend, might better characterise our relation to the changing climate. I make this argument through a reading of John Ashbery's late work because he encapsulates the particular forms of inattention and anxiety that saturate the contemporary atmosphere. Ashbery's poems are, in no typical sense, 'ecopoems', and the criticism his work invites is only incidentally 'eco'. In this way, I make an argument about the incidental ecopoem that offers insight insofar as it captures the psychical stakes of states of bewilderment on our ability to think the future.